LBGTQ+ crime and victimization - Bernat, Frances P. (Routledge, Taylor & Francis Group, 2023)
This book provides research and analysis on an understudied topic: the LBGTQ+ community as victims and offenders. Most publications focus on LBGTQ+ history and the community's movement towards equality and acceptance in society and in law. A focus on how the criminal justice system victimizes and marginalizes LBGTQ+ persons is needed. Consequently, this work includes chapters on members of the LBGTQ+ community who work in the criminal justice system, forced sexual orientation efforts, transgender legal concerns, LBGTQ+ persons who are arrested and imprisoned, and online dating hate crimes. International scholars provide their individual stories about being gay, bisexual or lesbian and working as a police or correctional officer. Other international contributors explain their research on crime and how the law and criminal justice community does not provide LBGTQ+ persons with protection or support as offenders or victims. This book will of interest to researchers and advanced students of Criminology, Sociology, Law, and Gender Studies. It was originally published as a special issue of the journal Women & Criminal Justice